KEKASARAN PERMUKAAN RESIN-MODIFIED GLASS IONOMER CEMENT SETELAH PERENDAMAN DALAM AIR SUNGAI (Penelitian Menggunakan Air Sungai Desa Anjir Pasar, Barito Kuala, Kalimantan Selatan) - Permatasari, Anindya Putri; Ichrom Nahzi, Muhammad Yanuar; Widodo, Widodo (FKG Unlam, 2016)
ABSTRACT Background:Resin-modified glass ionomer cement is a hybrid form of glass ionomer cement and resin. Added resin (HEMA) in this material allows its characteristics to improve, especially its resistance of acid.The water of Desa Anjir Pasar River has acidic nature with pH as low as 3-5.Purpose: The aim of this studywas to find surface roughness difference of resin modified glass ionomer cement after being soaked in the water of Anjir Pasar Village River compared to aquadest-soaked materials.Method:This study was true experimental used posttest only with control group design. Samples used resin-modified-glass ionomer cement specimenswhich were prepared in cylindrical-shaped with diameter of 10 mm and thickness of 2 mm. One groupwassoaked in aquadest (control) andanother group in river water with pH of 4,07for 4,5 days (equivalent to 3 years of exposure) before measuring the surface roughness of each group. Data was analyzed using parametric analysis Independent T-Test 95% (α = 0,05) which presented p value = 0,03 (p<0,05). Result:The result indicated that there was a significant difference of surface roughness between resin modified glass ionomer cement soaked in the water of Anjir Pasar Village River with pH of 4,07 for 4,5 daysand in the aquadest.Conclusion: Based on this study it was concluded that resin-modified glass ionomer cement which soaked with river water has higher surface roughness that resin-modified glass ionomer cement which soaked with sterile aquadest. Keywords: Resin-Modified Glass Ionomer Cement, river water, surface roughness ABSTRAK Latar Belakang:Resin-modified glass ionomer cement merupakanhybrid dari glass ionomer cement dengan resin. Penambahan bahan resin (HEMA) memperbaiki sifatnya, yaitu ketahanan terhadap asam.Air Sungai Desa Anjir Pasar memiliki karakteristik asam dengan rentang pH 3-5.Tujuan:Tujuan penelitian ini untukmengetahuiperbedaan kekasaranpermukaanbahanresin-modified glass ionomer cement setelahdilakukanperendaman dalam air Sungai Desa Anjir Pasar dan akuades steril. Metode: Penelitian ini merupakan penelitian eksperimental murni dengan rancangan posttest only with control group design. Sampel penelitian ini menggunakan spesimen resin-modified glass ionomer cement dibuat berbentuk silindris dengan diameter 10 mm dan ketebalan 2 mm. Masing-masing kelompok direndam dalam akuades steril (kontrol) dan air sungai pH 4,07 selama 4,5 hari (sama dengan 3 tahun pemaparan), kemudian dihitung kekasaran permukaannya. Data diuji menggunakan analisis parametrik Independent T-Test 95% (α = 0,05) dan didapatkan p=0,03 (p<0,05). Hasil: Hasil penelitian menunjukkan bahwa terdapat perbedaan kekasaran permukaan yang bermakna pada resin-modified glass ionomer cement antara perendaman dalam air sungai pH 4,07 selama 4,5 dengan perendaman dalam akuades steril.Kesimpulan: terdapat perbedaan kekasaran yang lebih besar pada bahan resin-modified glass ionomer cement yang direndam dalam air sungai daripada yang direndam akuades steril. Kata-kata kunci: Resin-modified Glass Ionomer Cement, Air Sungai, Kekasaran Permukaan